Limit load interaction of pipe bends under moment and pressure loadings [electronic resource] - 421116 Sew, Suh Fen (2007)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2007